Knowledge, determinants and use of modern contraceptives among married women in Sabon Gari Zaria, Northern Nigeria - Aliyu, A.; Tukur, Dahiru; Adegboyega, M. Oyefabi; Ladan, Muhammad Awwal (Oxford University Press, 2015)
Introduction: Improving reproductive health of young women in least developed countries requires access to safe and effective contraceptive methods. We conducted a study on knowledge, determinants and use of modern contraceptives among married women in Sabon Gari, Zaria-Northern Nigeria.